Normal and anomalous diffusion in a bouncing ball over an irregular surface - Boscolo, Ana Laura [UNESP]; Junior, Valdir Barbosa Da Silva [UNESP]; Barreiro, Luiz Antonio [UNESP] (American Physical Society (APS), 2023)
The problem of a bouncing ball on a nonplanar surface is investigated. We discovered that surface undulation adds a horizontal component to the impact force, which acquires a random character. Some aspects of Brownian motion are found in the horizontal distribution of the particle. On the x axis, normal and superdiffusion are observed. For the probability density's functional form, a scaling hypothesis is presented.